Probe and kit for early diagnosis of diffuse large B-cell lymphoma - ZHAO ZIJIAN; YIN SIYI; DING DING (2024)
The invention provides a probe specifically bound with CD138, a kit and a micro-fluidic chip containing the probe, and a method for diagnosing diffuse large B-cell lymphoma in a subject by using the probe, the kit or the micro-fluidic chip. The present disclosure also provides a method of screening a probe for diagnosing diffuse large B-cell lymphoma. 本公开提供了与CD138特异性结合的探针，包含探针的试剂盒和微流控芯片，以及使用探针、试剂盒或微流控芯片诊断受试者中弥漫性大B细胞淋巴瘤的方法。本公开还提供了筛选用于诊断弥漫性大B细胞淋巴瘤的探针的方法。